Rubén Gallo. Proust’s Latin Americans. Baltimore: Johns Hopkins UP, 2014. 280 pp. - Eric Touya de Marenne (Studies in 20th & 21st Century Literature, 2015)
Review of Rubén Gallo. Proust’s Latin Americans. Baltimore: Johns Hopkins UP, 2014. 280 pp.
Keywords: Marcel Proust; Latin Americans